Questionnaire Measures and Physiological Correlates of Presence: A Systematic Review - Grassini, Simone; Laumann, Karin (Frontiers in Psychology, 2020)
The published literature has produced several definitions for presence, as well as various methods for measuring it. The variety of conceptualizations makes it difficult for researchers to interpret, compare, and evaluate presence ratings obtained from individual studies. Presence has been measured by employing questionnaires, physiological indexes, behavioral feedbacks, and interviews. A systematic literature review was conducted to provide insight into the definitions of presence and measurements in studies from 2002 to 2019, with a focus on questionnaires and physiological measures. The review showed that scholars had introduced various definitions of presence that often originate from different theoretical standpoints. This fact has produced a multitude of different questionnaires that aim to measure presence, making the construct itself challenging to grasp and operationalize for future researchers. At the same time, physiological studies that investigate the physiological correlates between presence and subjective self-reports have not been replicated. Most of the scholars have preferred the use of questionnaires, with Witmer and Singer’s Presence Questionnaire being the most prevalent. Among the physiological measures, electroencephalography and skin conductance were most frequently used. This review aimed to highlight the current research on the topic and stimulate future structured efforts to standardize the use of the construct of “presence” and replicative efforts of previous studies to help disentangle the complicated relationship between physiological indexes and presence.